District and city. city-planning historiography and the question of the dominion of reference. the case of lima (2006)
The definition and delimiting of an object of study for the historical investigation of the residential urbanism, is a question of permanent controversy. Does it really exists an object of particular and pre-established study? Which are the components, the limits and the structures of functioning of this object of reference? The text is a presentation of the theoretically empirical aspects related to the identification of an object of pertinent study for the investigation of the contemporary Lima residential urbanism. Close to an evaluation of the situation of the Peruvian urban historiography recently dedicated to Lima; the notions of city and neighborhood turn into basic referents for the dentification of the different urbanistic traditions (state urbanism, private urbanism and urbanism of slums). The neighborhood in its urban dimension appears as the basic unit in order to historify.